HYPERCHOLESTEROLEMIA SUPPRESSES KIR CHANNELS IN PORCINE BONE MARROW PROGENITOR CELLS IN VIVO - Mohler, Emile R. (2007)
OBJECTIVE: Inwardly-rectifying K(+) (Kir) channels are responsible for maintaining membrane potentials in a variety of cell types including endothelial cells where they modulate endothelium-dependent vasorelaxation. The goal of this study is to determine the functional expression of Kir channels in porcine bone marrow-derived side population (BM-SP) cells that demonstrate phenotypes of endothelial progenitor cells (EPCs). We further asses the hypercholesterolemia sensitivity of Kir channels in BM-SP cells, which may play a key role in hypercholesterolemia-mediated regulation of EPCs. METHODS: To assess the effect of hypercholesterolemia on Kir channels in BM-SP, Kir currents were recorded in SP cells sorted from the bone marrow of healthy or hypercholesterolemic animals. RESULTS: We found Kir channels constitute the major conductance in porcine bone marrow-derived side population (BM-SP) cells. These cells are defined by their efficiency of Hoechst dye efflux and have been reported to differentiate into multiple cell lineages including endothelium in vivo. We demonstrate here that porcine BM-SP cells differentiate to an endothelial lineage (CD31+, vWF+) supporting the hypothesis that these cells are endothelial progenitor cells. Also, BM-SP cells express Kir with biophysical properties recapitulating those in mature endothelial cells, but with a much higher current density. Flow cytometric (FACS) analysis indicated that the number of SP cells was unaffected by hypercholesterolemia. However, hypercholesterolemia significantly inhibited Kir channels in BM-SP cells. CONCLUSIONS: We successfully demonstrate that BM side population cells represent an origin of endothelial progenitor cells. This study further shows, for the fist time, that the functional expression of Kir channels in bone marrow (BM) -derived SP. Moreover, we demonstrate that hypercholesterolemia condition significantly suppresses the Kir channels in BM-SP cells, suggesting that hypercholesterolemia-mediated regulation of Kir channels may be an important factor not only in dysfunction of mature endothelium but also in dysfunction of BM-SP cells.